Keberkesanan Modul Enam Roda Pengurusan Terhadap Bisnes Kecil Berdasarkan Tematik Keusahawanan Dalam Hadith Al-Sahihayn - Abdul Basit Abdur Rahim Nasution; Aminudin Hehsan; Zulkiflee Haron; Mohd Khairul Nizam Zainan Nazri (Usuli Faqih Research Centre PLT, 2024)
The objective of this conceptual paper is to introduce and highlight the six-wheel drive business management module that has benefited 11,000 business owners from 2016-2017. Most business entrepreneurs today failed to expand their businesses because they fail to fully understand the business or company management system. This qualitative research is conducted around the Klang Valley, Kuala Lumpur and Selangor, Malaysia. Researchers used interviews, observations and analysis of documents for information. Data and information were analyzed using ATLAS.ti software.The findings show that 80% of business entrepreneurs who have been practicing the six-wheel management module managed to streamline the company system and achieved high sales in less than two years. Additionally, this paper also proposes a framework of research that future researchers can use in studying the effects of this six-wheel module on economic development especially in Malaysia.